WAKALAH BI AL-ISTISMAR DALAM PANDANGAN DSN MUI - Syapar Alim Siregar, Sawaluddin Siregar, Liska Agustina Siregar (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2021)
The definition of wakalah bi Al-istismar contract is a contract used in several products on the capital market, such as sukuk and mutual funds. This contract includes the renewal of the wakalah contract combined with the investment contract. While the purpose of wakalah bi al-istismar, which is where someone represents a party so that he invests his funds, either with or without compensation. This wakalah law is in accordance with the permitted MUI DSN. In this contract scheme, initially it was related to investors or what was called muwakkil giving power to representatives or proxies in making investments, both managing and developing their funds. Then the representative who invests the funds owned by the muwakkil of the party who authorizes it with several contracts that are in accordance with sharia principles. Then from the investment produces the name of the result or risk in it. All these results and risks are the rights and responsibilities of the authorizer and the last stage is the refund to the muwakkil.